Elastic biodegradable starch/ethylene-co-vinyl alcohol fibre-mesh scaffolds for tissue engineering applications - Susano, Maria A. (2014)
The fabrication of a biomaterial scaffold, with adequate physical and structural properties for tissue engineering applica- tions, is reported. A blend of starch with ethylene-vinyl alcohol (50/50 w/w, SEVA-C) is used to produce 3D fibre-mesh scaffolds by wet-spinning. The scaffolds are characterized in terms of morphology, porosity, interconnectivity, and pore size, using scanning elec- tron microscopy (SEM) and microcomputed tomography (µCT). The degradation behavior, as well as the mechanical properties of the scaffolds, is investigated in presence of alpha-amylase enzyme at physiological concentration. Scaffolds with porosities ranging from 43 to 52%, interconnectivity of ≈70.5% and pore size between 118 and 159 µm, can be fabricated using the proposed methodology. The scaffolds exhibit an elastic behavior in the wet state with a compressive modulus of 7.96 ±0.32 MPa. Degradation studies show that SEVA-C scaffolds are susceptible to enzymatic degradation by alpha-amylase, confirmed by the increase of weight loss (40% of weight loss after 12 weeks) and presence of degradation products (reducing sugars) in solution. The diameter of SEVA-C scaffolds decreases with degradation time, increasing the overall porosity, interconnectivity and pore size. In vitro cell studies with human osteosarcoma cell line (SaOs-2) showed a nontoxic and cytocompatible behavior of the developed fibre mesh scaffolds. The positive cellular response, together with structural and degradable properties, suggests that 3D SEVA-C fibre-meshes may be good candidates as tissue engineering scaffolds.